Transformative Approaches in Safeguarding Children and Women: A Multidisciplinary Exploration - Gusman, Erry (Asosiasi Ide Bahasa Kepri, 2023)
Social harmony relies heavily on effective protection for children and women. In this context, transformative approaches are increasingly crucial for fostering sustainable change. This journal explores various multidisciplinary approaches in safeguarding children and women. Utilizing a broad conceptual framework, this article delves into novel strategies that promote positive shifts in understanding, protection, and empowerment of children and women. Through literature synthesis and empirical research, this journal aims to provide deep insights into how transformative approaches can be applied within the context of child and women protection. Practical implications of these findings are also discussed to contribute sustainably to policies and practices in this field.